The boy who escaped paradise : a novel - Yi, Chŏng-myŏng (Novelist) (Pegasus Books, 2016)
A "story of the mysteries, truths, and deceptions that follow the odyssey of Ahn Gilmo, a young math savant, as he escapes from the most isolated country in the world and searches for the only family he has left"--Amazon.com.